Open quantum system in external magnetic field within non-Markovian quantum Langevin approach; Physica A: Statistical Mechanics and its Applications; Vol. 514 - Abdurakhmanov B. Ilkhom; Kanokov Z. Zakirzhon; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2019, 2019)
Title screen